Insulin-Like Growth Factor 1 Receptor as a Therapeutic Target in Ewing Sarcoma: Lack of Consistent Upregulation or Recurrent Mutation and a Review of the Clinical Trial Literature. (28th January 2013) - O'Neill, Alison; Shah, Nilay; Zitomersky, Naamah; Ladanyi, Marc; Shukla, Neerav; Üren, Aykut; Loeb, David; Toretsky, Jeffrey
Abstract : The insulin-like growth factor 1 receptor (IGF-1R) has been considered an important therapeutic target in Ewing sarcoma (ES), generating a need to identify the subset of patients most likely to respond to IGF-1R inhibitors. We assessed IGF-1R expression in ES cell lines and patient tumors to understand the variable clinical responses to anti-IGF-1R therapy. Using ligand-binding displacement, we measured between 13, 000 and 40, 000 receptors per cell in ES cell lines. We used ELISA to quantify IGF-1R in patient tumors, which expressed 4.8%  ± 3.7 to 20.0%  ± 0.2 of the levels in a positive control cell line overexpressing IGF-1R. Flow cytometry showed markedly reduced IGF-1R expression in ES cell lines compared to a standard positive control cell line. The IGF1R gene was sequenced in 47 ES tumor samples and 8 ES cell lines; only one tumor sample showed a nonsynonymous mutation, R1353H, in a region with low functional impact. Finally, we assessed IGF-1R pathway activity in the ES stem cell (ESSC) population, to characterize its potential for resistance to anti-IGF-1R therapy, using Luminex technology. We found no significant differences in IGF-1R pathway activity between ESSCs and the total cell population. Overall, our findings suggest that IGF-1R as a therapeutic target in this sarcoma may require reevaluation.